Balancing acts: navigating disclosure of Meniere's disease during workplace socialization - Dewey, Andrew C., author; Williams, Elizabeth, advisor; Long, Ziyu, committee member; Conroy, Samantha, committee member (Colorado State University. Libraries, 2025)
This study explores how people with Ménière's Disease (MD), an episodic invisible disability, navigate disclosure during initial workplace socialization. Despite its profound impacts on communication, identity, and work-life balance, MD is unexamined within organizational communication literature. Drawing on theories of organizational socialization (Jablin, 2001) and Communication Privacy Management (Petronio, 2002), this qualitative study explored how people with MD constructed and managed privacy boundaries as they engaged with the first stages of the socialization process. Fifteen participants were recruited by an online support group and engaged in semi-structured interviews. Interview transcripts were analyzed through a phronetic iterative approach (Tracey, 2018; 2020), cyclically comparing participant responses with theoretical constructs. Data analyzed fell under two overarching categories: a) disability-influenced socialization; and b) the disclosure processes of people with MD. Themes under the socialization category included a) the influence of healthcare on the anticipatory socialization process; b) workplace communication about illness and disability; and c) the newfound process of conditional organizational identification. Findings under disclosure highlighted varying responses, including a) the refusal to disclose; b) the concept of involuntary disclosures; c) communication barriers to privacy management; d) reciprocal disclosures about chronic illness; e) opportunities to educate others on MD; and f) the renegotiation of boundaries following a privacy breach. Findings underscored the unique challenges that participants faced in the workplace. Disclosures were often influenced by previous medical experiences and the observed treatment of others with disabilities. This study contributes to scholarship by bridging organizational socialization and CPMT. A Model of Episodic Socialization is employed to understand theoretical intersections between invisible episodic disabilities, organizational socialization, and disclosure. Practical implications are offered for improving disability discourse in organizational contexts.
Keywords: health communication; organizational socialization; workplace disclosure; Ménière's disease; disability; privacy management